(untitled) (International Journal of Environmental Sciences, 2025)
Purpose: An exploration of the role of digital marketing in consumer purchase intentions within emerging markets for pharmaceutical products is presented in this study. Methodology: The study consists of positivist philosophy and follows inductive reasoning in descriptive approach to assessing this relationship. There was a quantitative survey of a sample of 50 people in a specified emerging market with a 12-item questionnaire. Findings: The data, analysed with the help of IBM SPSS, indicated very weak and statistically insignificant correlation between digital marketing and purchase intention (r -0.055, p > 0.05). This implies that there is no straightforward correlation between these variables and therefore that other variables might have a greater impact in determining the purchase of pharmaceutical products. Value: The importance of the study is an emphasis on the missing link in existing literature regarding emerging markets and insights that can change the traditional notions of digital marketing effectiveness in this market domain.